When design is inspired by theatre: acting techniques as prospective design methods - Roberge, Jacynthe; Sperano, Isabelle; Rivenbark, Leigh; Rubio, Daniel Caja (My University, 2021)
In acting training, psychophysical exercises are used to strengthen the relationship between mind and body, thus fostering a deeper understanding of the character [1]. Intrigued and inspired by the potential value of these techniques in design contexts, we explored their application for interaction designers as research methods in a pedagogical setting. To do so, we first created a single-session workshop that introduced design students to basic actor movement techniques in the winter of 2019. The goal of the workshop was to help students empathize with their users and discover solutions when designing digital products. Later, in the fall of 2020, we used reflections from the first activity to develop two longer workshops; both consisted of three sessions and were carried out consecutively in two different universities. In this article, we present a case study of those three workshops. After discussing considerations for the evolution of the workshops, we describe how each was conducted. Finally, we share our findings and insights that arose throughout the process.
Keywords: Interaction design; acting techniques; prospective ergonomics; design methods